The effect of implementing a government financial information management system (GFMIS) on the effectiveness of budget implementation - Haneen Ali Yousif; Salaheldeen Moammed AL- Emam (Journal of Madenat Alelem University College, 2022)
The paper aimed to find out the effect of implementing the Government Financial Information Management System (GFMIS) on the effectiveness of budget implementation. In order to reach the goal, the researcher designed a questionnaire that was distributed to a group of accountants, managers and employees in the departments of the Ministry of Finance, namely the Budget Department, the Accounting Department, the Administration Department, the Economic Department and the Information Technology Department, where the study sample consisted of (110) people. The researcher used the statistical package for studies. Seince (SPSS). data entry and analysis. Descriptive statistics and inferential statistics were used to reach the results of the study, the results showed that there is a positive impact of statistical significance for the application of the government financial information management system in improving government financial management systems (budget execution system, payments and receipts system), And in light of the results of the study that have been reached the study recommended the necessity of increasing the departments' interest and knowledge in applying the government financial information management system (GFMIS) because of its multiple functions for planning, control and decision-making in a wider manner, developing the Internet and data base and developing the computers used in the ministries and government departments that apply the government financial information management system. To improve the level of its performance and give it the required speed to keep pace with the development of the accounting environment and to serve the management in the areas of planning and control.